Exogenous reinfection as a cause of multidrug-resistant and extensively drug-resistant tuberculosis in rural South Africa. - Andrews, Jason R; Gandhi, Neel R; Moodley, Prashini; Shah, N Sarita; Bohlken, Louise; Moll, Anthony P; Pillay, Manormoney; Friedland, Gerald; Sturm, A Willem (The Journal of infectious diseases, 2008)
Multidrug-resistant (MDR) and extensively drug-resistant (XDR) tuberculosis (TB) are now major threats in areas of South Africa with a high prevalence of TB and human immunodeficiency virus (HIV) infection. The role of exogenous reinfection as a cause of MDR and XDR TB in these settings has not been determined.
Keywords: Adult; Antitubercular Agents; Extensively Drug-Resistant Tuberculosis; Female; Genotype; HIV Infections; Humans; Male; Middle Aged; Mycobacterium tuberculosis; South Africa; Tuberculosis, Pulmonary